A complexidade das cláusulas relativas na fala espontânea do português do Brasil: Os dados do C-Oral Brasil - Crysna Bomjardim da Silva Carmo (2017)
Clausal relativization is a semantic-syntactic strategy that allows for natural languages to restrict/delimit a reference. In most natural languages, a relative clause exhibits a formal correlate. This is the case of Brazilian Portuguese (BP), whose syntactic pattern is post-nominal, i.e., the relative clause follows the referent N ([ N [QUE + finite verb]AdjP]NP). Traditionally, two relative clause strategies are identified in BP: restrictive clauses, which delimit the referent, and non-restrictive clauses, which do not delimit the referent. In view of that, this study aims to investigate relative clauses in BP spontaneous speech and then to propose a functional definition for clausal relativization based on prosody. Thus, this study consists of the following: it identifies the information structure of relative clauses in spontaneous speech, describes the processes of subordination characterizing these clauses, defines the semantic-cognitive operation involved in the relativization process, and, finally, describes relative clauses in spontaneous speech at the morphosyntactic level. Therefore, this study adopts an empirical approach, in harmony with Corpus Linguistics (MELLO, 2014; BERBER SARDINHA, 2004; HARDIE; MCENERY, 2002) and Descriptive Linguistics (PERINI, 2006, 2010). In this context, this study was carried out on a balanced sample of the C-ORAL BRASIL corpus (RASO; MELLO, 2012), the so-called minicorpus. Informationally tagged according to the Language into Act Theory (CRESTI, 2000), the minicorpus is available through the DB-IPIC platform (PANUNZI & GREGORI, 2011), which was used to extract the data here analyzed. The theoretical framework supporting this study comes from postulates by the Language into Act Theory (CRESTI, 2000, MONEGLIA; RASO, 2014) and Cognitive Linguistics (LANGACKER, 1987; FAUCONNIER & TURNER, 2002; SALOMÃO, 2005; MIRANDA, 2001). Accordingly, the following constructs are highlighted: domain of relativization vs. restricted subset (KEENAN & COMRIE, 1977); the relationship between instantiation and grounding and the notion of cognitive asymmetry (LANGACKER, 1987; 1991); the phenomenon of semantic scope (BARKER, 2015; NEGRÃO, 2003; SZABOLCSI; 2000) reset; the functionalist notion of dependency (HOPPER & TRAUGOTT, 1993); the juxtaposition as a syntactic procedure (RODRIGUES, 2015); and the information unit as a syntactic-semantic island (CRESTI, 2014). The results show that relative clauses in spontaneous speech: (i) exhibit complex and simple syntactic structures in the utterance; (ii) occur mainly in the Comment information unit; (iii) occur embedded in or isolated from a matrix clause in the utterance;(iv) exhibit great variability regarding the phrase structure of the referent N and the associated clause; (v) occur mainly in the syntactic position of direct object and adjunct of the matrix clause in the utterance; and(vi) only restrictive relative clauses, which occur linearized in spontaneous speech, constitute domains of relativization, since this is the only type of clause capable of establishing a background, in terms of a domain-scope for its interpretation, whereas non-restrictive relative clauses, which occur patterned in the utterance, do not establish such domain. Therefore, considering the informational, syntactic and semantic-cognitive levels, it is possible to state that these clauses do not constitute domains of relativization. Hence, non-restrictive relative clauses are referred to in this thesis as apositive clauses, and are still open for investigation.